Planejamento, análise espacial e otimização da localização das escolas públicas municipais de Montes Claros - MG - Rodrigo Marques do Nascimento (2021)
The accelerated urbanization of Brazilian cities, especially in the mid-twentieth century, imposed several challenges for the organization of urban space, which resulted in the convergence of a set of actions aimed at planning, democratizing and regulating interventions in the territory. Despite advances in this regard, some issues still do not have provisions in municipal plans, such as guidelines for defining the location of public schools. Therefore, the provision of the school network without being guided by criteria, mainly of accessibility, it can lead to long distances home-school, making students walk through long paths on foot or having to use motorized transport, which becomes chargeable, considering that the demand for public schools is mostly made up of low-income families. In this context, this research aims to propose an optimized location for municipal public schools in the city of Montes Claros - MG, using the facility location TransCAD tool, which applies the p-median problem and aims to reduce the average walking distance from home to school. Prior to indicating the solution, the aim is to understand the current scenario of the location of schools. For that, we seek to characterize the city of Montes Claros, MG, in relation to the demographic, socioeconomic and geographic profile of the resident population, using data from the Brazilian Institute of Geography and Statistics (IBGE), to identify the presence of spatial imbalances in the location of municipal public schools, by verifying the number of vacancies in schools and the distribution of the population, the criteria for allocation of students in schools available in the network, the accessibility of residents based on the indicators proposed by Brau, Mercê and Tarrago (1980), using the ArcGIS Service Area function and finally compare the location of existing municipal public schools in the city with the newly generated location. It should be noted that maps prepared in ArcGIS are used to represent this set of analyses. Therefore, the optimal location of schools is proposed in parallel with the definition of the school that is closest to every dwelling in the city, considering the configuration of the current school network. It was found out that there are spatial imbalances in the distribution of municipal schools in Montes Claros - MG, especially in the northwest region, which has a shortage of early childhood education schools, despite the fact that this area has an intense concentration of population between 0 and 5 years old. Regarding the current criteria for the allocation of students to their school, it appears that for early childhood education schools there may be hypotheses in which students are enrolled in schools that are not the closest to their residence. It is noted that the distance traveled by citizens to school is very low in most of the urban area. The optimized location proposal improves the accessibility of residents. The research presents fundamentals that corroborate for the reduction of the school trajectory in the city of Montes Claros - MG.